2021
DOI: 10.1111/ajd.13638
|View full text |Cite
|
Sign up to set email alerts
|

The alterations of gene expression of interleukin‐36α and interleukin‐37 between alopecia areata patients and healthy controls

Abstract: relatively short follow-up, the low sample size and the long-lasting response to the adalimumab originator at the time of the shift for many patients, the results are in line with previous comparability studies 1,3,4,5 and demonstrate that the biosimilar adalimumab has shown not to be less effective than the originator and the transition to biosimilar adalimumab in psoriasis patients treated with the originator is a safe and effective choice in a real-life setting of moderate to severe psoriasis patients as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Despite the Letter To The Editors e431 relatively short follow-up, the low sample size and the long-lasting response to the adalimumab originator at the time of the shift for many patients, the results are in line with previous comparability studies 1,3,4,5 and demonstrate that the biosimilar adalimumab has shown not to be less effective than the originator and the transition to biosimilar adalimumab in psoriasis patients treated with the originator is a safe and effective choice in a real-life setting of moderate to severe psoriasis patients as previously observed in other biologic treatments, in particular infliximab. 6 The only difference we observed was a significant worsening of the assessment of pain in a subpopulation of patients with BMI> 25 between T0 and T1 suggesting the need of further evaluations and objective data, also with a multi-specialist team.…”
mentioning
confidence: 62%
“…Despite the Letter To The Editors e431 relatively short follow-up, the low sample size and the long-lasting response to the adalimumab originator at the time of the shift for many patients, the results are in line with previous comparability studies 1,3,4,5 and demonstrate that the biosimilar adalimumab has shown not to be less effective than the originator and the transition to biosimilar adalimumab in psoriasis patients treated with the originator is a safe and effective choice in a real-life setting of moderate to severe psoriasis patients as previously observed in other biologic treatments, in particular infliximab. 6 The only difference we observed was a significant worsening of the assessment of pain in a subpopulation of patients with BMI> 25 between T0 and T1 suggesting the need of further evaluations and objective data, also with a multi-specialist team.…”
mentioning
confidence: 62%
“…Furthermore, IL-36 was reported to effectively reduce the production of melanin in human melanocytes (18) . The gene expression of IL-36α was significantly higher in both lesional in addition to non-lesional scalp biopsies of individuals with alopecia areata than in heathy controls, with a significant relation between the expression in alopecia areata lesions and the disease severity (19) .…”
Section: Discussionmentioning
confidence: 89%